Cracking mechanism in API 5L X65 steel in a CO2-saturated environment. (May 2019) - Silva, Samara Cruz da; de Souza, Eduardo Alencar; Pessu, Frederick; Hua, Yong; Barker, Richard; Neville, Anne; da Cunha Ponciano Gomes, José Antônio
Abstract: Hydrogen charging in low alloy steels poses a significant problem in the oil and gas industry. Detrimental hydrogen effects are not commonly expected in CO2 aqueous environments. However, the acid nature of these environments and the high corrosion rates expected justify the assessment of cracking susceptibility of carbon steel in a CO2 -saturated environment as presented in this work. The focus of this investigation is to understand how different surface films/corrosion products influence the hydrogen permeation and cracking mechanism of an API 5L X65 carbon steel in a saturated CO2 environment. The experiments were carried out to assess hydrogen permeation at open circuit potential on steel samples which were either wet-ground, or pre-filmed with iron carbide (Fe3 C) rich or iron carbonate (FeCO3 ) layers. Tafel measurements were also performed to determine the effect of the surface composition on the cathodic reactions. Slow strain rate tests (SSRT) were conducted in order to evaluate the effects of hydrogen on the cracking mechanisms of the steel in this sweet environment. Results indicated that at open circuit conditions, Fe3 C was able to increase the steady state hydrogen permeation current due to accentuation of the cathodic hydrogen-evolution reaction. Although FeCO3 suppressed the cathodic reaction at the steel surface, the development of the protective and densely packed crystalline layer increased hydrogen uptake marginally from that of the ground steel reduced. SSRT indicated a very moderate loss of ductility in wet-ground and FeCO3 steel surface conditions. However, a more significant reduction in area was observed in the tests carried out on Fe3 C rich samples. These results imply that a corroded API 5L X65 steel surface in a CO2 rich environment can enhance the hydrogen embrittlement (HE) susceptibility and as such, hydrogen permeation susceptibility needs to be considered in material selection. Highlights: API 5L X65 steel is susceptible to hydrogen embrittlement in pure CO2 environment. The embrittlement effects depend on the steel surface composition. Pre-corroded Fe3 C enriched surface increases hydrogen permeation. FeCO3 film surface does not reduce hydrogen permeation.